Chapter Useful knowledge, technological innovation and economic development in the European ceramic industries, 14th-18th centuries - Laliena Corbera, Carlos (Datini Studies in Economic History, 2023)
Ceramics have been essential in the domestic sphere and their production has undergone in the preindustrial era technological and cultural changes whose importance is obvious. This paper is to show in a very concise way how the production of European glazed ceramics underwent three phases of intense transformation of useful knowledge related to its production, with a successive accumulation leading to increasingly efficient results and a higher level of productivity. Moreover, it can be safely stated that, without this accumulation, the great progress of the 19th century in this area would have been impossible.